2011
DOI: 10.1002/pros.21433
|View full text |Cite
|
Sign up to set email alerts
|

Acute bacterial inflammation of the mouse prostate

Abstract: BACKGROUND Prostatic inflammation is gaining increasing attention as a potential etiologic factor in prostate cancer, benign prostatic hyperplasia, lower urinary tract symptoms, and CPPS. This study was performed to address the need for a well characterized model of acute prostatic inflammation that may be used to study the effect of acute inflammation on epithelial and stromal cell proliferation, voiding behavior, and neurovascular physiology. METHODS Uropathogenic E. coli 1677 was instilled transurethrally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
97
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(111 citation statements)
references
References 38 publications
11
97
1
Order By: Relevance
“…As described in detail in Materials and Methods, the CP9 E. coli and PBS control solutions were inoculated transurethrally into 9-wk-old wild-type C57BL/6 male mice. Consistent with previous reports, there were significantly variable degrees of inflammation among experimental mice and among different prostatic lobes (7,32). In addition, inflamed and noninflamed ducts often were observed concomitantly in all different lobes.…”
Section: Significancesupporting
confidence: 91%
See 1 more Smart Citation
“…As described in detail in Materials and Methods, the CP9 E. coli and PBS control solutions were inoculated transurethrally into 9-wk-old wild-type C57BL/6 male mice. Consistent with previous reports, there were significantly variable degrees of inflammation among experimental mice and among different prostatic lobes (7,32). In addition, inflamed and noninflamed ducts often were observed concomitantly in all different lobes.…”
Section: Significancesupporting
confidence: 91%
“…One reason for chronic inflammation in the prostate is bacterial colonization in the prostate via reflux of urine into the prostatic ducts of the peripheral zone (31). A reproducible mouse model of bacterial prostatitis has been established in which transurethral inoculation of uropathogenic strains of Escherichia coli into the prostate results in massive inflammation and reactive hyperplasia in the prostate (7,(32)(33)(34). As reported here, we established this mouse model for prostatitis using a uropathogenic E. coli strain CP9 that was isolated from the blood of a patient with pyelonephrititis (35).…”
Section: Significancementioning
confidence: 99%
“…Accordingly, studies have found an increased relative risk of prostate cancer in men with a prior history of certain sexually transmitted infections or prostatitis, which are often associated with intraprostatic inflammation (6,7). Furthermore, studies have indicated possible links between certain prostatic infections and inflammation (6,7,11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, inflammation has been proposed as a contributing factor to both prostate cancer initiation and progression (99,100), and it has been demonstrated that P. acnes and uropathogenic E. coli infections have been shown to strongly elicit inflammatory responses and enhance prostate cell proliferation (122)(123)(124) Together these results suggest that HHV-8 promotes an androgen-independent phenotype that does not require activation of and is potentially independent of the AR signaling pathway. Figure 6).…”
Section: Real-time Quantitative Reverse Transcription Pcr (Qrt-pcr) mentioning
confidence: 98%
“…Propionibacterium acnes and Escherichia coli infections of benign prostate cells induce significant changes in cell proliferation rates (122)(123)(124). However, to our knowledge, no studies have assessed how a chronic infection of malignant but otherwise androgensensitive prostate cells would affect disease course.…”
Section: Statement Of Problemmentioning
confidence: 99%